Intra sheath corticosteroid injection for De Quervain’s tenosynovitis - Pooswamy, Shanmuga Sundaram; Muralidharagopalan, Niranjanan Raghavn (International Journal of Research in Orthopaedics, 2019)
Background: De Quervain’s disease or stenosing tenosynovitis of the first dorsal compartment of the wrist is a common condition, which affects the Abductor pollicis longus and the extensor pollicis brevis tendons. There are characteristic signs and symptoms including a positive Finkelstein's test. Different options for treatment include conservative approaches like analgesics, splinting and physical therapy. If conservative options fail then steroid injection is considered. Methods: This is a retrospective study of single dose intra-sheath triamcinolone and lignocaine injection in 32 patients at our institute who were followed up for a period of 12 months. Results: In our study there were 25 females and 7 males with a mean age of 46.4±8.03 years. Right side was involved in 17 patients and left side in 15 patients. The pre procedure VAS score was 8.65±1.07. The follow up VAS scores at 1, 6 and 12 months respectively were 1.4±1.14, 0.84±1.06 and 1.03±1.26 respectively. 4 out of 32 patients had positive Finkelstein’s test at 1 year follow up. Common complications were pain at injection site, which was seen in 5/32 patients and depigmentation seen in 2/32 patients. Conclusions: Thus intra sheath triamcinolone injection is a safe and effective procedure for treatment of De Quervains disease.